KONSEP KEPEMIMPINAN DALAM GURU PENGGERAK - Sukma Elia; Ahmad Fauzan; Fisman Bedi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to describe the concept of leadership in teacher mobilisers. This research is a qualitative research with literature review type. Information collection was carried out by searching for several important sources including primary sources of literature sources that discuss the concept of leadership in the driving teacher and several other literature sources related to the research. The data collected was then analysed so as to obtain the results of the study which showed that the role of the teacher as a leader is an interactive, consultative, parsitive and controlling figure. in the concept of the driving teacher model in a structured education policy formation to produce teachers as leaders of the teaching and learning process in the future with efforts to implement a curriculum that is dressed in Ki Hajar Dewantara's educational philosophy.